A study on the impact of health shocks on subjective wellbeing of middle-aged people and older adults—Evidence from China - Xu, Qinglin; Gu, Jinghong; Jia, Cangcang; Chen, Huiying; Li, Zihao; Gu, Hai (Frontiers in Public Health, 2024)
The health issues that afflict middle-aged people and older individuals are a significant factor that affects their quality of life. It is crucial to investigate the impact of health shocks on the subjective well-being of this demographic and the mechanisms that underlie this impact to promote healthy aging.This study utilized data from the China Family Panel Study in 2018 and 2020 to analyze the effects of HSs and their categories on the subjective well-being of middle-aged people and older individuals using the propensity score matching difference-in-differences method. Additionally, the study explored the mediating role of social participation. The findings indicate that health shocks, both chronic and acute, diminish the subjective well-being of middle-aged people and older adults. Furthermore, these shocks have a more significant negative effect on the subjective well-being of individuals aged 60 and above, women in the middle-aged and older demographic, individuals in rural areas who belong to the middle-aged and older age groups, and individuals possessing activities of daily living. The mechanism analysis revealed that health shocks, both chronic and acute, reduce the subjective well-being of middle-aged people and older individuals by disrupting partnerships. Lowering the possibility of health shocks, the government should build a strong health management system and improve the health insurance system to enable timely treatment for persons suffering from health shocks. Individuals and families should live healthy lives and engage in social activities to avoid health shocks and improve subjective well-being.